METODE ALTERNATIF ANALISIS INSEKTISIDA PERTANIAN DELTAMETHRIN MENGGUNAKAN KROMATOGRAFI CAIR KINERJA TINGGI PENGGUNAAN KOLOM C-18, FASE GERAK ASETONITRIL 80% DALAM AKUABIDES, LAJU ALIR FASE GERAK 1,6 ML/MENIT, DAN PANJANG GELOMBANG DETEKTOR UV-VIS 190 NM ( - Donny Satria, R. Gagak; Sumiarto, Bambang; Trisyono, Andi; Wijayanti, Agustina Dwi (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2013)
Deltamethrin is a common pesticide used in plants and animals. Research about this pesticide has been done with various methods. The purpose of this research was to validate the alternative test method of deltamethrin using High Performance Liquid Chromatography (HPLC). This research used pure deltamethrin. The tool in this research was HPLC Shimadzu 6.1 with 80% acetonitrile in aquabides for mobile phase, flow rate 1.6 ml/min and uv-vis detector wavelength 190 nm. The data were analyzed by calculated the average, standard deviation, and relative standard deviation. The results showed the average area for each concentration of 0.1 ug/ml, 0.25 ug/ml, 0.3 ug/ml, 0.5 ug/ml, 0.75 ug/ml, 1 ug/ml,2 ug/ml, and 5 ug/ml, were 52806.33, 119070.3, 137758.3, 220292, 339677.3, 449448.7, 856049.3, and 2,177,558, with a linear equation y = 43283x + 8455, R = 0,999. It could be concluded that the method is valid based on precision, acuration, specificity, limit of detection, limit of quantification, and linearity.